Method for controlling porosity of spacer layer of perovskite solar cell and application

By using a physical mixing method of pore-forming agent suspension and zirconium oxide and other materials in perovskite solar cells, a zirconium oxide spacer layer with a specified porosity is formed, which solves the problem of insufficient porosity control in the existing technology and improves efficiency. Battery fill factor and efficiency.

CN119343023APending Publication Date: 2025-01-21HUBEI WONDER SOLAR LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661273.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art cannot effectively regulate the porosity of the zirconia spacer layer of perovskite solar cells, resulting in carrier loss and inefficiency of the battery.

Method used

The pore-forming agent suspension is physically mixed with zirconium oxide, cellulose, environmental additives and a second solvent to form a zirconium oxide layer slurry, and is calcined to form a spacer layer to control porosity and crystallinity.

Benefits of technology

The pores with a specified size and uniform distribution are provided on the interval layer, optimizing the crystalline orientation of the orerite layer, and improving the concentration of the carrier and the battery efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343023A_ABST
    Figure CN119343023A_ABST
Patent Text Reader

Abstract

The invention provides a method for controlling the porosity of a spacer layer of a perovskite solar cell and application of the method. The method comprises the following steps: (1) providing a pore-forming agent suspension, wherein the pore-forming agent suspension is obtained by dispersing a pore-forming agent in a first solvent; (2) physically and uniformly mixing zirconium oxide, cellulose, an environmental additive, a second solvent and the pore-forming agent suspension to obtain zirconium oxide primary pulp; and (3) filtering the zirconium oxide raw slurry, performing rotary evaporation to obtain zirconium oxide layer slurry, and placing the zirconium oxide layer slurry on the surface of the electron transport layer of the perovskite solar cell to form a zirconium oxide layer. According to the method provided by the invention, the perovskite crystallinity of the spacer layer in the perovskite solar cell can be improved, specified uniformly distributed pores are formed in the spacer layer, and the efficiency of the perovskite solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a method for controlling the porosity of a spacer layer of a perovskite solar cell and an application thereof. Background Art

[0002] The internal structure of a perovskite solar cell includes a substrate material / conductive glass, an electron transport layer (commonly used material titanium dioxide), a perovskite layer, and a conductive cathode (conductive metal or carbon electrode). When receiving sunlight, the perovskite layer first absorbs photons to generate electron-hole pairs and form excitons. Uncompounded electrons and holes are collected by the electron transport layer and the spacer layer, respectively, and finally absorbed by the FTO of the conductive glass and the conductive cathode, respectively. This will result in carrier loss. How to avoid or reduce carrier loss can improve the efficiency of perovskite solar cells. For the perovskite absorption layer (spacer layer), the crystallographic orientation of the perovskite structural material will affect the efficiency of the cell. At the same time, the carrier concentration generated by the amount of light energy absorbed by the perovskite layer can also determine the efficiency of the cell.

[0003] As a zirconium oxide electronic paste used in the preparation of perovskite solar cells, it can be formed into the required structure and thickness by printing, coating or spraying, and can retain a considerable portion of pores and voids after calcination and solvent diffusion. However, this method that cannot adjust the porosity cannot achieve a more perfect fit when the perovskite crystallizes and improve the filling factor.

[0004] For the structure of the zirconium oxide spacer layer of the perovskite absorption layer, the introduction of a pore former and the control of its porosity are important factors affecting the efficiency performance of solar cells. A pore former is an additive that creates a pore structure in the material. Its essence is a substance that is easily decomposed into gas. In the normal preparation process of perovskite solar cells, the printing, coating or spraying of zirconium oxide slurry can form the required structure and thickness, and a considerable part of the pores and pores can be retained after calcination and solvent vaporization. However, this method that cannot adjust the porosity cannot achieve a more perfect fit during the crystallization of perovskite and improve the filling factor. In September 2022, the research group of Professor Luo Jianqiang of East China University of Technology used urea as a porosity regulator and used a simple spraying method to prepare a porous zirconium oxide spacer layer for three-layer perovskite solar cells. The porosity and thickness of the spacer layer are adjusted by adjusting the ratio of zirconium oxide to the pore former urea and the number of spraying cycles. However, this type of method cannot obtain the desired and more accurate porosity.

[0005] How to qualitatively control the porosity of the zirconia layer to obtain a porosity that is more consistent with perovskite crystallization requires further improvement. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. At present, as the pore structure required for improving the crystallization of perovskite on the zirconium oxide spacer layer of the perovskite solar cell, the pores left after the swelling, dissolution and calcination of cellulose and solvents of different sizes or types, such as the number average and weight average, are still used to adapt the crystallization orientation of the perovskite in the layer. This method has technical disadvantages such as random pores, uneven sizes, and too small pore range; at the same time, as the insulating layer zirconium oxide, the single zirconium oxide has a weak reflection ability for sunlight after penetrating the electron transport layer on the solar cell glass, and fails to fully reflect the unused photons for secondary absorption of the dye on the titanium dioxide. The present invention provides a method for controlling the porosity of the spacer layer of the perovskite solar cell. The method provided by the present invention is used to improve the perovskite crystallinity of the spacer layer in the perovskite solar cell, and can provide a pore of a specified size and uniform distribution on the spacer layer, optimize the degree of crystallization of the perovskite on the spacer layer, and provide a reflective layer to promote the perovskite layer to generate more carriers, and finally complete the problem of increasing the efficiency of the perovskite solar cell.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] In a first aspect of the present invention, a method for controlling the porosity of a spacer layer of a perovskite solar cell is provided, comprising:

[0009] (1) providing a pore-forming agent suspension, wherein the pore-forming agent suspension is obtained by dispersing the pore-forming agent in a first solvent;

[0010] (2) physically mixing zirconium oxide, cellulose, an environmental additive, a second solvent and the pore-forming agent suspension to obtain a zirconium oxide slurry;

[0011] (3) filtering the zirconium oxide slurry, and obtaining a zirconium oxide layer slurry after rotary evaporation, and placing the zirconium oxide layer slurry on the surface of the electron transport layer of the perovskite solar cell to form a spacer layer.

[0012] According to some embodiments of the present invention, the pore-forming agent in step (1) is selected from at least one of polypropylene spheres or modified derivatives thereof, polyethylene spheres or modified derivatives thereof, polyvinyl chloride or modified derivatives thereof, polyvinyl alcohol (PVA) or modified derivatives thereof, polymethyl methacrylate (PMMA) or modified derivatives thereof, polyvinyl butyral (PVB) or modified derivatives thereof, urea microspheres or modified derivatives thereof, or polystyrene (PS) microspheres or modified derivatives thereof.

[0013] According to some embodiments of the present invention, the particle size of the pore former is 20-500 nm.

[0014] According to some embodiments of the present invention, the pore-forming agent carries a modified group, and the modified group is selected from at least one of a hydroxyl group, a carboxyl group, an amide group, an aldehyde group, an amino group, and a carbonyl group.

[0015] According to some embodiments of the present invention, the first solvent is selected from at least one of ethylene glycol, glycerol, polyethylene glycol, styrene, perchloroethylene, trichloroethylene, ethylene glycol ether, triethanolamine, and terpineol ether.

[0016] According to some embodiments of the present invention, the particle size of the zirconium oxide in step (2) is 20-150 nm.

[0017] According to some embodiments of the present invention, the cellulose is selected from at least one of methyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, or a mixture of multiple celluloses of different viscosity grades.

[0018] According to some embodiments of the present invention, the viscosity of the cellulose is 5-150 cp.

[0019] According to some embodiments of the present invention, the environmental additive is one or more of citric acid, oxalic acid, hydroxybenzoic acid, acetic acid, pyruvic acid, butyric acid, and glycine.

[0020] According to some embodiments of the present invention, the second solvent is selected from at least one of methanol, ethanol, ethylene glycol, ethyl acetate, butyl acetate, acetone, and diethyl ether.

[0021] According to some embodiments of the present invention, in step (2), the mixture is evenly mixed by ball milling, sand milling, or ultrasound, and the mass ratio of zirconium oxide: cellulose: environmental additive: pore-forming agent suspension: second solvent is 1: (0.1-1): (2-50): (0.1-2): (10-300).

[0022] According to some embodiments of the present invention, the zirconia slurry obtained in step (3) has a solid content of 10-40% and a viscosity of 3000-250000 cp.

[0023] A second aspect of the present invention provides a zirconium oxide layer, which is formed by calcining the zirconium oxide layer slurry prepared by the method described in the first aspect.

[0024] A third aspect of the present invention provides a perovskite solar cell, comprising:

[0025] Basal layer;

[0026] A conductive layer, wherein the conductive layer is located on the surface of the base layer;

[0027] A dense layer, wherein the dense layer is located on the surface of the conductive layer;

[0028] An electron transport layer, wherein the electron transport layer is located on the surface of the dense layer;

[0029] The spacer layer is located on the surface of the electron transport layer, and the spacer layer is the zirconium oxide layer mentioned in the second aspect.

[0030] The counter electrode layer is located on the surface of the spacer layer.

[0031] The beneficial effects achieved by the present invention are at least:

[0032] The present invention provides a method for controlling the porosity of a perovskite solar cell spacer layer, so as to improve the perovskite crystallinity of the spacer layer in the perovskite solar cell, overcome the shortcomings of the existing technology, provide a pore of a specified size and uniform distribution on the spacer layer, optimize the crystal orientation of the perovskite on the spacer layer, provide more sunlight reflection, increase the generated carrier concentration, and finally achieve the problem of improving the filling factor of the battery (such as the improvement of the FF filling factor in Table 4) and the increase of the efficiency of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic structural diagram of a perovskite solar cell provided according to an embodiment of the present invention, wherein reference numeral 11 is a substrate layer, 12 is a conductive layer, 13 is a dense layer, 14 is an electron transport layer, 15 is a spacer layer, and 16 is a counter electrode layer. DETAILED DESCRIPTION

[0034] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0035] The spacer layer prepared by the prior art has technical disadvantages such as random pores, uneven sizes, and too small a pore range. At the same time, due to the disadvantage of too small a pore range, the scattering ability of sunlight is not greatly enhanced, and the carrier concentration enhancement effect on the perovskite layer is low. The purpose of the present invention is to provide a method for controlling the porosity of the spacer layer of a perovskite solar cell, which is used to adjust the porosity of the spacer layer, improve the filling factor of the perovskite solar cell, and thus improve the cell efficiency.

[0036] The present invention provides a method for controlling the porosity of a spacer layer of a perovskite solar cell, comprising:

[0037] (1) providing a pore-forming agent suspension, wherein the pore-forming agent suspension is obtained by dispersing the pore-forming agent in a first solvent;

[0038] (2) uniformly mixing zirconium oxide, cellulose, an environmental additive, a second solvent and the pore-forming agent suspension to obtain a zirconium oxide slurry;

[0039] (3) filtering the zirconium oxide slurry, and obtaining a zirconium oxide layer slurry after rotary evaporation, and placing the zirconium oxide layer slurry on the surface of the electron transport layer of the perovskite solar cell to form a spacer layer.

[0040] The method provided by the present invention is used to control the porosity of the spacer layer by introducing a pore-forming agent suspension and compounding it with zirconium oxide, cellulose and environmental additives. Cellulose has multiple functions in preparing slurry, such as film-forming, thickening, pore-forming ability, and the ability to completely decompose and volatilize after calcination without residue, which can effectively change the original properties of the slurry. It is widely used in the preparation of slurry for electronic devices.

[0041] According to a specific embodiment, the particle size of the zirconium oxide is 20-150 nm. Compared with traditional insulating materials such as magnesium oxide, aluminum oxide, iron oxide, scandium oxide, and silicon oxide, zirconium oxide of this particle size has excellent high dielectric constant, high band gap, film strength, and reliable porosity for film formation. The cellulose mentioned can be non-toxic methyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, etc., and the national standard viscosity of cellulose is between 5-150cp.

[0042] The pore-forming agent used includes, but is not limited to, polypropylene balls, polyethylene balls, polyvinyl chloride, polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), polyvinyl butyral, urea microspheres or polystyrene balls and at least one of the modified derivatives of these substances. According to a preferred embodiment, the pore-forming agent is a polystyrene ball, and the particle size of the polystyrene ball is 20-500nm. In the specific experimental process, due to the strong self-assembly ability of the polystyrene nanospheres themselves, it is difficult to form a uniform and stable suspension in a polar solvent, and the viscosity of the solvent also has a great influence on its own dispersion ability. Therefore, the experiment is to first prepare the PS nanospheres into a uniform and stable suspension, and then add them to the normal process of preparing the insulating layer slurry. Of course, under the premise of meeting the experimental conditions, it can be a high-concentration monodisperse alcohol solution or a pure powder substance.

[0043] Since polystyrene spheres have strong self-assembly ability, when selecting polystyrene spheres, they can be directional modified and can have one or more of the following groups: hydroxyl (-OH), carboxyl (-COOH), amide, aldehyde (-CHO), amino (-NH2), carbonyl (-CO), etc.

[0044] In the step 1, when preparing a uniform and stable pore-forming agent suspension, the solvent can be an organic solvent with high viscosity such as ethylene glycol, glycerol, polyethylene glycol, styrene, perchloroethylene, trichloroethylene, ethylene glycol ether, triethanolamine, pinene alcohol ether, etc., to ensure stable dispersion of PS nanospheres.

[0045] In the step 2, the zirconium oxide slurry is independently configured for different perovskite solutions, so for the perovskite solution system of different solvents such as AM and FM, the zirconium oxide slurry can be configured according to the ratio of zirconium oxide: cellulose: pine alcohol: acetic acid: ethanol 1: (0.1-1): (2-50): (10-300). Of course, the available solvent can be not only ethanol, but also methanol, ethylene glycol, ethyl acetate, butyl acetate, acetone, ether, etc. Available environmental additives can be not only acetic acid, but also one or more of citric acid, oxalic acid, hydroxybenzoic acid, pyruvic acid, butyric acid, and glycine. The "many" mentioned herein includes two or more.

[0046] The solid content of the prepared pore-forming agent zirconium oxide slurry should be 10-40%, and the viscosity should be 3000-250000cp. The preparation of zirconium oxide slurry includes but is not limited to ball milling, sand milling, ultrasonic treatment and other principle treatments.

[0047] The present invention also provides a zirconium oxide layer, which is formed by calcining the zirconium oxide layer slurry prepared by the method described above.

[0048] The present invention also provides a perovskite solar cell, such as Figure 1 As shown, including:

[0049] Basal layer 11;

[0050] A conductive layer 12, wherein the conductive layer 12 is located on a surface of the base layer 11;

[0051] A dense layer 13, wherein the dense layer 13 is located on the surface of the conductive layer 12;

[0052] An electron transport layer 14, wherein the electron transport layer 14 is located on the surface of the dense layer 13;

[0053] A spacer layer 15, the spacer layer 15 is located on the surface of the electron transport layer 14, and the spacer layer 15 is the zirconium oxide layer mentioned above;

[0054] The counter electrode layer 16 is located on the surface of the spacer layer 15 .

[0055] The substrate material mentioned may be a commonly used substrate material in the art, and the substrate may be any one of FTO glass, ITO glass or silicon wafer. The dense layer may be used to better connect the electron transport layer and the conductive layer.

[0056] The material of the electron transport layer mentioned above can be any one of TiO2, SnO2, ZnO, C60 and its derivatives, C70 and its derivatives, or non-fullerene and its derivatives. For example, it can be TiO2.

[0057] The counter electrode layer is a commonly used metal or highly conductive material, including but not limited to any one of Au, Ag, Al, Cu or carbon.

[0058] The perovskite solar cells mentioned in this article can be single-junction perovskite cells or tandem perovskite cells. Tandem perovskite cells mean that the perovskite layers can be stacked on top of each other or on top of traditional crystalline silicon solar cells to form a "tandem" cell that can absorb a wider solar spectrum.

[0059] The prepared zirconium oxide layer is the spacer layer, which can be used to adjust the efficiency and filling factor of the battery by adjusting the performance of the spacer layer. For example, by introducing pore-forming agents of different particle sizes, different zirconium oxide slurries are prepared to obtain zirconium oxide layers of different particle sizes and different addition amounts, thereby adjusting the efficiency and filling factor of the battery. According to a preferred embodiment, this experiment uses hydroxyl-modified polystyrene (PS) nanospheres as the pore-forming agent of the zirconium oxide layer, and its particle size is 20-500nm (the experimental plan is 20, 50, 100, 150, 200, 300, 500nm). Experimental steps:

[0060] 1. Preparation of a uniform and stable pore-forming agent suspension: Weigh a certain amount of hydroxyl-modified PS nanospheres with a certain particle size, slowly add them to a certain amount of pineneol while stirring and heating at 60°C, and when they are relatively dispersed and no large particles are suspended, move them into an ultrasonic rod device for ultrasonic dispersion for 1 hour. A uniformly dispersed and stable oleyl alcohol suspension is prepared.

[0061] 2. Prepare stably dispersed ball-milled zirconium oxide slurry: weigh zirconium oxide, 10 ethyl cellulose, 50 ethyl cellulose, acetic acid, ethanol, etc. according to a certain ratio and in order, add them to the same volume of the ball mill, and then add them according to the proportion of the amount of the added pore-forming agent suspension to ensure that the entire solution does not exceed 3 / 4 of the volume of the ball mill, and then start ball milling. When designing the experiment, control the amount of pore-forming agent added and control different ball milling times when setting the ball milling parameters for experimental comparison.

[0062] 3. Preparation of zirconia layer slurry with hydroxyl-modified PS nanospheres: Obtain the above-mentioned stably dispersed ball-milled zirconia slurry, filter it through a nylon filter cloth to remove impurities, and then transfer it to a rotary evaporator and rotary evaporate it with no more than 3 / 4 volume of the solution.

[0063] 4. Prepare 10*10cm 2Perovskite solar cells: According to the normal preparation process of perovskite solar cells, the TiO2, ZrO2 and C layers are correctly brushed in order, and finally the preparation of perovskite solar cells is completed after calcination and filling with perovskite solution for aging and crystallization.

[0064] The technical scheme of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. Unless otherwise specified, the reagents used in the examples can be obtained commercially.

[0065] Example 1

[0066] Example 1 A perovskite solar cell is prepared by the following method, comprising:

[0067] 1. Preparation of a uniform and stable pore-forming agent suspension: According to the addition of 0%, 10% and 20% of the mass of zirconium oxide powder (10g), 80nm hydroxyl-modified polystyrene (PS) nanospheres were weighed and slowly added to 60g of pine alcohol while stirring and heating at 60°C. When the nanospheres were relatively dispersed and no large particles were suspended, they were transferred to an ultrasonic rod device for ultrasonic dispersion for 1h. 60g, 61g and 62g of uniformly dispersed stable pine alcohol suspensions were prepared respectively.

[0068] 2. Prepare stably dispersed ball-milled zirconium oxide slurry: Add zirconium oxide, ethyl cellulose N-10, ethyl cellulose N-50, acetic acid, and ethanol to a 500 ml ball mill of the same volume in sequence, and then add all the pore-forming agent suspension prepared in step 1 to the same ball mills of different numbers, ensuring that the total solution does not exceed 3 / 4 of the volume of the ball mill, and start ball milling.

[0069] 3. Preparation of zirconia layer slurry with hydroxyl-modified PS nanospheres added: The above-mentioned stably dispersed ball-milled zirconia slurry was obtained, filtered through a nylon filter cloth to remove impurities, and then transferred to a 1L rotary evaporator.

[0070] 4. Prepare 10*10cm 2 Perovskite solar cells: According to the normal preparation process of perovskite solar cells, the TiO2, ZrO2 and C layers are correctly brushed in order, and finally the preparation of perovskite solar cells is completed by calcining ZrO2 and filling perovskite solution for aging and crystallization.

[0071] The prepared perovskite solar cell was characterized as follows, and the results are shown in Table 1, where the values ​​in brackets in Table 1 are used as standard samples for comparison. The values ​​in parentheses are used as standard samples for comparison

[0072] Table 1 Results of two experiments

[0073]

[0074] Combined with the results in Table 1, it can be seen that the zirconium oxide layer added with PS pore former has the effect of improving the filling factor and battery efficiency in the entire battery system.

[0075] Example 2

[0076] Example 2 A perovskite solar cell is prepared by the following method, comprising:

[0077] 1. Preparation of a uniform and stable pore-forming agent suspension: According to the addition of 0%, 10% and 20% of the mass of zirconium oxide powder (10g), 0g, 1g and 2g of hydroxyl-modified PS nanospheres of 100nm size were weighed and slowly added to 60g of pine alcohol while stirring and heating at 60°C. When it was relatively dispersed and no large particles were suspended, it was moved into an ultrasonic rod device for ultrasonic dispersion for 1h. 60g, 61g and 62g of uniformly dispersed stable pine alcohol suspensions were prepared respectively.

[0078] 2. Prepare stably dispersed ball-milled zirconium oxide slurry: weigh zirconium oxide, ethyl cellulose N-10, ethyl cellulose N-50, acetic acid, and ethanol in order and add them into a 500 ml ball mill of the same volume. Then add all the pore-forming agent suspension prepared in step 1 into the same ball mills of different numbers, ensuring that the total solution does not exceed 3 / 4 of the volume of the ball mill, and start ball milling.

[0079] 3. Preparation of zirconia layer slurry with hydroxyl-modified PS nanospheres added: The above-mentioned stably dispersed ball-milled zirconia slurry was obtained, filtered through a nylon filter cloth to remove impurities, and then transferred to a 1L rotary evaporator.

[0080] 4. Prepare 10*10cm 2 Laminated perovskite solar cells: According to the normal preparation process of perovskite solar cells, the TiO2, ZrO2 and C layers are correctly brushed in order, and finally the preparation of perovskite solar cells is completed by calcining ZrO2 and filling perovskite solution for aging and crystallization.

[0081] The prepared perovskite solar cell was characterized as follows, and the results are shown in Table 2 (the values ​​in brackets in Table 2 are used as standard samples for comparison).

[0082] Table 2 Results of two times

[0083]

[0084] It can be seen from the results given in Table 2 that the zirconium oxide layer added with the PS pore former has the effect of improving the filling factor and battery efficiency in the entire battery system.

[0085] Example 3

[0086] 1. Preparation of a uniform and stable pore-forming agent suspension: Weigh 20% of the mass of the added zirconium oxide powder (10g) of 100nm, 150nm, 200nm, 300nm and 500nm hydroxyl-modified PS nanospheres, 2g each, and slowly add them to 60g of pine alcohol while stirring and heating at 60°C. When they are relatively dispersed and no large particles are suspended, move them into an ultrasonic rod device for ultrasonic dispersion for 1h. 62g of a uniformly dispersed stable oleyl alcohol suspension is prepared.

[0087] 2. Prepare stably dispersed ball-milled zirconium oxide slurry: weigh zirconium oxide, ethyl cellulose N-10, ethyl cellulose N-50, acetic acid, ethanol, etc. in order and add them into a 500ml ball mill of the same volume, then add all the added pore-forming agent suspension into the same ball mills of different numbers, making sure that the total solution does not exceed 3 / 4 of the volume of the ball mill, and start ball milling.

[0088] 3. Preparation of zirconia layer slurry with hydroxyl-modified PS nanospheres added: The above-mentioned stably dispersed ball-milled zirconia slurry was obtained, filtered through a nylon filter cloth to remove impurities, and then transferred to a 1L rotary evaporator.

[0089] 4. Prepare 10*10cm 2 Perovskite solar cells: According to the normal preparation process of perovskite solar cells, the TiO2, ZrO2 and C layers are correctly brushed in order, and finally the perovskite solar cells are prepared after ZrO2 calcination and filling with perovskite solution.

[0090] The results are shown in Table 3 (the values ​​in brackets in Table 3 are used as standard samples for comparison).

[0091] Table 3

[0092]

[0093] From the results given in Table 3, it can be seen that at the same addition amount, adding 150nm PS spheres has the best effect.

[0094] Example 4

[0095] Example 4 The results of adding different amounts of 150 nm hydroxyl-modified PS nanospheres were compared with the method described in the above examples, as shown in Table 4 below (the values ​​in brackets are used as standard samples for comparison).

[0096] Table 4 Hydroxyl modified PS nanospheres 10*10cm 2 Quantitative experiments

[0097]

[0098] Combined with the results in Table 4, it can be seen that the gradual increase and inflection point of the filling factor FF correspond one to one with the addition amount of PS balls, which further illustrates the optimal addition amount of PS balls and the optimal improvement degree of the filling factor (15%) when gradually increasing the filling factor.

[0099] In the description of this specification, the reference terms "one embodiment", "some embodiments", "specific implementation" and the like mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention.

[0100] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for controlling the porosity of a spacer layer of a perovskite solar cell, characterized in that: include: (1) providing a pore-forming agent suspension, wherein the pore-forming agent suspension is obtained by dispersing the pore-forming agent in a first solvent; (2) physically mixing zirconium oxide, cellulose, an environmental additive, a second solvent and the pore-forming agent suspension to obtain a zirconium oxide slurry; (3) filtering the zirconium oxide slurry, and obtaining a zirconium oxide layer slurry after rotary evaporation, and placing the zirconium oxide layer slurry on the surface of the electron transport layer of the perovskite solar cell to form a spacer layer.

2. The method according to claim 1, characterized in that The pore-forming agent in step (1) is selected from at least one of polypropylene spheres or modified derivatives thereof, polyethylene spheres or modified derivatives thereof, polyvinyl chloride or modified derivatives thereof, polyvinyl alcohol (PVA) or modified derivatives thereof, polymethyl methacrylate (PMMA) or modified derivatives thereof, polyvinyl butyral (PVB) or modified derivatives thereof, urea microspheres or modified derivatives thereof, or polystyrene (PS) microspheres or modified derivatives thereof.

3. The method according to claim 1, characterized in that The particle size of the pore-forming agent is 20-500 nm; The pore-forming agent has a modified group, and the modified group is selected from at least one of a hydroxyl group, a carboxyl group, an amide group, an aldehyde group, an amino group, and a carbonyl group.

4. The method according to claim 1, characterized in that The first solvent is selected from at least one of ethylene glycol, glycerol, polyethylene glycol, styrene, perchloroethylene, trichloroethylene, ethylene glycol ether, triethanolamine, and terpineol ether.

5. The method according to claim 1, characterized in that The particle size of the zirconium oxide in step (2) is 20-150 nm.

6. The method according to claim 1, characterized in that The cellulose is selected from at least one of methyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose, or a mixture of multiple celluloses of different viscosity grades; Optionally, the cellulose has a viscosity of 5-150 cp.

7. The method according to claim 1, characterized in that The environmental additive is one or more of citric acid, oxalic acid, hydroxybenzoic acid, acetic acid, pyruvic acid, butyric acid, and glycine; the second solvent is at least one of methanol, ethanol, ethylene glycol, ethyl acetate, butyl acetate, acetone, and ether; Optionally, in step (2), the mixture is mixed evenly by physical means such as ball milling, sand milling, or ultrasound, and the mass ratio of zirconium oxide: cellulose: environmental additive: pore-forming agent suspension: second solvent is 1: (0.1-1): (2-50): (0.1-2): (10-300).

8. The method according to claim 1, characterized in that The zirconia slurry obtained in step (3) has a solid content of 10-40% and a viscosity of 3000-250000 cp. 9 . A zirconium oxide layer, wherein the zirconium oxide layer is formed by calcining the zirconium oxide layer slurry prepared by the method according to claim 1 .

10. A perovskite solar cell, characterized in that: include: Basal layer; A conductive layer, wherein the conductive layer is located on the surface of the base layer; A dense layer, wherein the dense layer is located on the surface of the conductive layer; An electron transport layer, wherein the electron transport layer is located on the surface of the dense layer; A spacer layer, the spacer layer is located on the surface of the electron transport layer, and the spacer layer is the zirconium oxide layer according to claim 9; The counter electrode layer is located on the surface of the spacer layer.